The Influence of Online Purchases by Dormitory Residents on Dormitory Management - Putri, Adelia Mahayani; Bahri, Bahri; Astuti, Widi (LPPM STIAB Jinarakkhita Lampung, 2025)
This study aims to analyse the influence of online purchases by dormitory residents on dormitory management. A descriptive correlational quantitative approach was applied with 75 dormitory residents selected through purposive sampling. The research instrument included a questionnaire, with online purchase indicators including frequency, type, and resident satisfaction, while dormitory management indicators included operational efficiency, logistics management, and service quality. The research findings show that online purchasing has a significant impact on dormitory management, with a regression coefficient of 0.881 indicating a positive relationship between the variables. In addition, the R Square value of 0.495 indicates that 49.5% of the variability in dormitory management is explained by online purchasing activities, while the remaining 50.5% is influenced by other factors. Online purchasing makes it easier for residents to fulfil their daily needs without having to leave the residence hall, but it also presents challenges for management in terms of logistics, transaction security, and resident satisfaction with the quality of the product or service. This study highlights the importance of integrating digital technology and adaptive management systems to support residents' needs. In conclusion, online purchasing has a positive impact on the operational efficiency and quality of dormitory management. The findings provide guidance for dormitory managers to improve services and overcome challenges in managing online purchasing activities.